Impact of uniform illumination in widefield microscopy and mesoscopy - Mete Aslan; Alexander J. Gray; Logan Packard; Caeden Giorgetta; Irving J. Bigio; M. Selim Ünlü (Scientific Reports)
Abstract Illumination uniformity is critical for widefield optical microscopy, especially for high-throughput and accurate quantitative imaging of biological specimens. While traditional Köhler illumination improves uniformity, it often fails to deliver homogeneous intensity across large fields of view. Existing optical and computational correction techniques remain inadequate for a broad range of quantitative imaging applications. Here, we implement a novel illumination device that we call the “effective uniform color-light integration device” (EUCLID), quantifying improvements in two widefield imaging modalities that require uniform illumination. For both imaging modalities, we demonstrate significantly improved precision of quantitative measurements compared to traditional Köhler illumination. The EUCLID device, which can also provide uniform spectral mixing, can be readily adapted to many other widefield imaging modalities to enhance imaging accuracy and reliability, with low cost and ease of implementation.